Healthcare Engineering Proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Shorey, Rajeev; Ghosh, Purnendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book contains the proceedings of CAETS 2015 Convocation on 'Pathways to Sustainability: Energy, Mobility and Healthcare Engineering' that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about 'Healthcare' and includes 11 chapters on diverse topics like regenerative engineering, big data analytics in healthcare, molecular science, rising expenditure on health issues, adoption of personalized medicine, etc. The contents of this volume will be useful to researchers and healthcare professionals. .
Chapter 1. Ethics-Based-Engineering: Importance of Academy's Initiative toward Human Security and Well-Being -- Chapter 2. Scalable Medical Devices: Personal and Social -- Chapter 3. Therapeutic Platforms for Ischemic and Traumatic Brain Injuries across National-level Neuroimaging Grids -- Chapter 4. Next Generation Devices and Technologies through Regenerative Engineering -- Chapter 5. Rising Healthcare Spending: Is Technology the Solution? -- Chapter 6. Big Data Analytics and Molecular Medicine -- Chapter 7. Can Life Sciences Progress without Engineering? -- Chapter 8. Evaluation of BMP-2 Mediated Bone Formation using Enzymatically Crosslinkable Injectable Hydrogels: An In vivo Study using Transgenic Fluorescent Reporter Mouse Model -- Chapter 9. Supporting the Diagnosis of Childhood Pneumonia in Low Resource Settings -- Chapter 10. Adoption of Personalized Medicine: Towards Identifying Critical Changes -- Chapter 11.Biophysics-based Markers Surpassing Biochemical Markers in Screening of Ageing-related Neurodegeneration and Cognitive Impairment.
Keywords: Biomedical engineering; Medical sciences; Health services administration; Biomedical Engineering and Bioengineering; Health Sciences; Health Care Management